The Role Of Interesting Problems In Teaching Students Mathematics - Nafasov Ganisher Abdurashidovich; Eshkuvatov Kozim (Genius Journals, 2024)
In this article, the role of interesting tasks in teaching students mathematical operations in mathematics lessons is to stimulate at least a slight interest in mathematics among students. As a result, the level of students' mathematical knowledge increases, and they begin to study all topics of mathematics more deeply
Keywords: monotone; convex; section; polynomial